Quantification and validation of HPLC‐UV and LC‐MS assays for therapeutic drug monitoring of ertapenem in human plasma. (14th October 2012) - Pickering, Matthew; Brown, Stacy
ABSTRACT: Rapid and simple HPLC‐UV and LC‐MS methods were developed and validated for the quantification of ertapenem (Invanz™) in human plasma. Ertapenem is a unique drug in that current dosing recommendations call for a 1 g dose for normal renal function patients, despite body weight. These assays, which involve a protein precipitation followed by liquid–liquid extraction, allow for fast therapeutic drug monitoring of ertapenem in patients, which is especially useful in special populations. Both methods were sufficient to baseline resolve meropenem (internal standard) and ertapenem, and were validated over 3 days using a six‐point calibration curve (0.5–50 µg/mL). Validation was collected using four different points on the calibrations curve yielding acceptable precision (<15% inter‐day and intra‐day; <20% for lower limit of quantitation, LLOQ) as well as accuracy (<15% inter‐day and intra‐day; <20% for LLOQ). The lower limit of detection (LOD) was determined to be 0.1 and 0.05 µg/mL for the HPLC‐UV and LC‐MS methods, respectively. The developed HPLC‐UV and LC‐MS methods for ertapenem quantification are fast, accurate and reproducible over the calibration range and can be used to determine ertapenem plasma concentrations for monitoring clinical efficacy. Copyright © 2012 John Wiley & Sons, Ltd.